(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Zinc oxide nanoparticles (ZnO NPs) are widely employed in various industries and research institutions due to their significant applications as antioxidants, anti-inflammatory and anti-diabetic medicines. However, the conventional synthesis methods face environmental and economic challenges, leading to the exploration of alternative approaches. Among these alternatives, the biological synthesis method utilizing plant sources has emerged as a promising option, offering numerous health, environmental, economic, and medicinal benefits. ZnO NPs manufactured from plant derivatives have unique features that promote agricultural efficiency, such as the production of chemical fertilisers, chemical insecticides, and fumigants. Such Phyto synthesized ZnO NPs have widespread use in the manufacture of chemicals having anticancer, antiseptic and antifungal properties. Strobilanthes alternata is used in Indonesia to solve urinary problems, check and repair hemorrhages, halt diarrhea, and cure sexual infections. The leaves and stem extracts of Mimosa diplotricha, have been applied topically to enhance wound healing within conventional medicine. The substance in the plant is thought to have anti-inflammatory and antibacterial qualities. This review offers a succinct explanation of the significance of these two medicinal plants in the synthesis of ZnO NPs and its applications in agriculture, medicine, and textiles. The antibacterial and photocatalytic activities of the nanoparticles isolated from the two plant species, will also help the researchers in the future